Determinants and Strategies for Exports of Agri-Food Firms (영문판) - 조성주 (농식품 기업의 수출 결정 요인 및 전략 분석, 2019)
As a result of the proliferation of FTAs (Free Trade Agreements), both imports and exports of agri-food have been expanding daily. Thus the importance of policies impacting agri-food exports has increased in terms of their effect on companies entering and applying the global value chain, associating agriculture and food industry, developing new markets, and creating jobs. It is therefore important to develop systematic export strategies in the farming industry. Unfortunately, there are insufficient studies evaluating domestic agri-food firms as leading export entities in this continuously developing overseas market. For this reason, this study analyzed the factors affecting agri-food companies entering and staying in the export market, and strategies influencing export performance. Based on the results of this analysis, we present policy implications for strategic determinants of export performance, effective strategies for each type of agri-food firm, and for export support programs.